HUBUNGAN TINGKAT GEMAR MEMBACA (TGM) DENGAN KETERSEDIAAN KOLEKSI DI DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN PADANG PARIAMAN - Fitriazmi Zikrillah R; Elva Rahmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Promoting a culture of reading is an important aspect of community literacy development, but this is often influenced by the availability of library collections. This study aims to analyze the relationship between reading levels and the availability of collections at the Padang Pariaman District Archives and Library Office. The main question of the study is whether there is a significant relationship between these two variables. The study used a quantitative approach with a correlational descriptive design. A sample of 99 respondents was determined using simple random sampling, and data were collected using a Likert scale-based questionnaire that had been tested for validity and reliability. The results of the analysis show that there is a positive and significant relationship between reading enthusiasm and collection availability, with a correlation coefficient of 0.631 (strong category) and a contribution of 39.8% to the variation in collection availability. These findings confirm that the higher the reading culture of the community, the better the perception of library collection availability. This study has implications for the development of relevant and up-to-date collection-based literacy strategies, but it is still limited to a small sample size and does not include other external variables.